1991
DOI: 10.1103/physrevd.44.3136
|View full text |Cite
|
Sign up to set email alerts
|

Scalar field, nonminimal coupling, and cosmology

Abstract: We study the dynamics of a flat Friedmann-Robertson-Walker universe filled with a self-interacting scalar field nonminimally coupled to the gravitational field. Dynamical equations for the system can be derived from a pointlike Lagrangian. For this system an additional Nother symmetry exists provided that the coupling constant 6 is equal to 0 or i. When l= $ the scalar potential has to be constant. In this case we obtain an exact solution. We also analyze the behavior of the scalar field when S f 0, i .Most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 19 publications
(9 reference statements)
0
34
0
Order By: Relevance
“…Over the decades, Noether symmetry has been found to play important roles in explaining the cosmic evolution [24][25][26][27][28][29][30][31][32]. However, for a non-minimally coupled scalar-tensor theory of gravity, a metric independent conserved current is admissible directly from the field equations in general, which is not realized from Noether symmetry [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Over the decades, Noether symmetry has been found to play important roles in explaining the cosmic evolution [24][25][26][27][28][29][30][31][32]. However, for a non-minimally coupled scalar-tensor theory of gravity, a metric independent conserved current is admissible directly from the field equations in general, which is not realized from Noether symmetry [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In that paper the existence of point symmetries in the cosmological field equations was considered. A point symmetry of a set of coupled differential equations may be identified by defining a vector field [38,42,43] X ≡ X n ∂ ∂q n + dX n dt When a cosmological constant is present, it can be shown that point symmetries only exist in the field equations of the Brans-Dicke theory and, moreover, that such symmetries arise in types I, II, VI 0 and VII 0 , but not for the types VIII and IX [41]. It is interesting that the same class A types admit duality symmetries and this suggests that these dualities may be related to the point symmetries.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that symmetries can play an important role to select viable cosmological models [18][19][20][21]. In the framework of the so-called Noether Symmetry Approach [21][22][23] it is possible, in principle, to find out cyclic variables related to conserved quantities and then to reduce cosmological dynamics.…”
Section: Introductionmentioning
confidence: 99%